Metal-containing MFI-type zeolite and catalyst for hydrocarbon production
A metal-containing MFI type zeolite catalyst with tailored mesopore distribution and acid content addresses the challenges of catalyst stability and productivity in producing aromatic and light hydrocarbon compounds from aliphatic hydrocarbons, achieving efficient and long-lasting hydrocarbon conversion.
Patent Information
- Application Number
- JP2021006158
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-19
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-01-19
AI Technical Summary
Existing catalysts for producing aromatic compounds from aliphatic hydrocarbons face challenges in terms of productivity, stability, and catalyst life, particularly when producing light hydrocarbon compounds simultaneously.
A specific metal-containing MFI type zeolite catalyst is developed, characterized by a uniform mesopore distribution, specific metal introduction, and optimized acid content, which enables simultaneous and stable production of light hydrocarbon compounds and aromatic compounds from aliphatic hydrocarbons.
The catalyst achieves excellent productivity and long catalyst life, maintaining high yields of both light hydrocarbon compounds and aromatic compounds, thereby improving the efficiency and cost-effectiveness of the hydrocarbon conversion process.
Smart Images

Figure 0007661702000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a metal-containing MFI type zeolite having a specific metal introduced therein and a catalyst for producing hydrocarbons comprising the same, and in particular to a specific metal-containing MFI type zeolite having a relatively uniform group of mesopores, and a catalyst for the simultaneous production of light hydrocarbon compounds and aromatic compounds which exhibits excellent performance in terms of productivity, stability and long life when producing aromatic compounds from aliphatic hydrocarbons, and which enables the simultaneous production of C2-C3 hydrocarbon compounds. [Background technology]
[0002] MFI zeolite is used as a highly selective catalyst that utilizes uniform pores derived from the zeolite structure. Examples of using MFI zeolite as a catalyst include disproportionation of toluene (see, for example, Patent Document 1) and isomerization of xylene (see, for example, Patent Document 2).
[0003] These reactions mainly utilize the characteristics of the micropores in MFI zeolite, which have an entrance diameter of approximately 0.5 nm and are thought to be effective reaction sites for molecules with molecular diameters close to the pore diameter.
[0004] Furthermore, research is being conducted on MFI zeolites having pores larger than micropores (less than 2 nm), that is, mesopores (pore diameter 2 to 50 nm) (see, for example, Non-Patent Document 1).
[0005] As a promising material for industrial use, a new MFI type zeolite with uniform mesopores of 10 nm or more and a method for producing the same have been proposed (see, for example, Patent Document 3). However, there have been only a few reports of specific results being obtained by using zeolites with mesopores as catalysts, particularly in reactions using relatively small molecules with 10 or less carbon atoms as raw materials.
[0006] Benzene, toluene, and xylene (hereinafter, collectively referred to as aromatic compounds) are often obtained by decomposing feedstock oil (e.g., naphtha, etc.) obtained by petroleum refining in a thermal cracking reactor, and separating and refining aromatic compounds from the obtained thermal cracking products by distillation or extraction. In the production of aromatic compounds by these production methods, aliphatic hydrocarbons (including paraffinic, olefinic, acetylene, and alicyclic) are included as thermal cracking products other than aromatic compounds. Therefore, since aliphatic hydrocarbons are simultaneously produced along with the production of aromatic compounds, the production amount of aromatic compounds is adjusted according to the production amount of aliphatic hydrocarbons, and the production amount is naturally limited. In addition, aromatic compounds can be produced by contacting an aliphatic hydrocarbon raw material with a catalyst mainly containing medium pore size zeolite at a temperature of about 400°C to about 800°C (for example, see Non-Patent Documents 2 to 5). Compared with the production method of aromatic compounds by thermal cracking, this production method has the advantage that it has low added value and can produce aromatic compounds from surplus hydrocarbon raw materials. Catalysts for use in the production of these aromatic compounds have also been developed. For example, as a catalyst for producing aromatic compounds using hydrocarbons containing paraffins, olefins, and naphthenes as raw materials, a zinc-supported medium pore size zeolite catalyst with reduced zinc scattering has been provided (see, for example, Patent Document 4). In addition, as a catalyst for producing aromatic compounds using paraffins, olefins, acetylene-based hydrocarbons, cyclic paraffins, and cyclic olefins as raw materials, a catalyst in which platinum and a halogen component are simultaneously supported on L-type zeolite has been provided (see, for example, Patent Document 5). Furthermore, a catalyst for aromatization reaction has been provided, which is characterized in that zinc and / or gallium are supported on a structure having a size of 0.1 to 100 mm, a crystalline porous aluminosilicate present on the surface layer of the structure, and an inorganic support present in the inner layer except for the surface layer of the structure (see, for example, Patent Document 6). In addition, catalysts for producing aromatic compounds using hydrocarbons as raw materials have been provided (see, for example, Patent Documents 7 and 8). In recent years, there have been developed aromatic compound production catalysts containing specific MFI type zeolites (see, for example, Patent Document 9), and silver-containing zeolites having high heat resistance and hydrothermal resistance (see, for example, Patent Document 10).) etc. have been proposed. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 4014279 [Patent Document 2] Patent No. 2598127 [Patent Document 3] JP 2013-227203 A [Patent Document 4] Japanese Patent Application Publication No. 10-33987 [Patent Document 5] Patent No. 3264447 [Patent Document 6] Patent No. 5447468 [Patent Document 7] Patent No. 3966429 [Patent Document 8] Patent No. 5564769 [Patent Document 9] JP 2017-127857 A [Patent Document 10] JP 2018-154538 A [Non-patent literature]
[0008] [Non-Patent Document 1] Microporous and Mesoporous Materials, Vol. 137, p. 92 (2011) [Non-Patent Document 2] Industrial & Engineering Chemistry Research, Vol. 31, p. 995 (1992) [Non-Patent Document 3] Industrial & Engineering Chemistry Research, Vol. 26, p. 647 (1987) [Non-Patent Document 4] Applied Catalysis Vol. 78, p. 15 (1991) [Non-Patent Document 5] Microporous and Mesoporous Materials, Vol. 47, p. 253 (2001) Summary of the Invention [Problem to be solved by the invention]
[0009] However, in the methods for producing aromatic compounds using catalytic reactions proposed in Patent Documents 4 to 8, there was a problem in terms of production costs with respect to catalyst life (the time from when the catalyst is active after the start of the reaction until it becomes inactive). In addition, the proposals in Patent Documents 9 and 10 were effective in terms of producing aromatic compounds, but no consideration was given to the production of light hydrocarbons.
[0010] The present invention provides a novel catalyst that enables the simultaneous, selective and long-term stable production of light hydrocarbon compounds and aromatic compounds from aliphatic hydrocarbons having relatively small molecules (particularly those having a carbon number of 10 or less, preferably 4 to 6), and a metal-containing MFI type zeolite that can be used therein. [Means for solving the problem]
[0011] Means for Solving the Problems The present inventors have conducted intensive research to solve the above problems, and as a result have found that a specific MFI type zeolite having a specific metal introduced therein can serve as a catalyst that makes it possible to selectively and stably produce light hydrocarbon compounds and aromatic compounds simultaneously from aliphatic hydrocarbons over a long period of time, thereby completing the present invention.
[0012] That is, the present invention relates to a metal-containing MFI type zeolite characterized by satisfying the following characteristics (i) to (vi), and a catalyst for simultaneously producing light hydrocarbon compounds and aromatic compounds comprising the same. (i) The metal is at least one metal selected from the group consisting of molybdenum, manganese, iron, cobalt, nickel, palladium, platinum, zinc and gallium. (ii) The mesopore distribution curve has a peak, the half width (hw) of the peak is hw≦20 nm, the center value (μ) of the peak is 10 nm≦μ≦20 nm, and the mesopore volume (pv) of the mesopores corresponding to the peak is 0.05 ml / g≦pv. (iii) In powder X-ray diffraction measurement at a diffraction angle of 2θ, there is no peak in the range of 0.1 to 3 degrees. (iv) The average particle diameter (PD) is PD≦100 nm. (v) The amount of outer surface acid is 0.0001 to 0.01 mmol / g. (vi) The acid amount is 0.02 to 0.85 mmol / g.
[0013] The present invention will be described in detail below.
[0014] The metal-containing MFI type zeolite of the present invention is a specific MFI type zeolite having at least one metal selected from molybdenum, manganese, iron, cobalt, nickel, palladium, platinum, zinc, and gallium introduced therein, and is particularly useful as a catalyst for the simultaneous production of light hydrocarbon compounds and aromatic compounds, which enables the simultaneous, selective, and long-term stable production of light hydrocarbon compounds and aromatic compounds from aliphatic hydrocarbons.
[0015] The metal-containing MFI zeolite of the present invention is a metal-containing MFI zeolite that satisfies the above (i) to (vi), and (i) contains at least one metal selected from molybdenum, manganese, iron, cobalt, nickel, palladium, platinum, zinc, and gallium, thereby becoming a zeolite that exhibits excellent performance as a catalyst for simultaneous production of light hydrocarbon compounds and aromatic compounds, and preferably contains zinc, since it is particularly suitable as a catalyst for simultaneous production of ethane and aromatic compounds with good bounce. In this case, the content of the metal is preferably 0.05 to 15 wt%. In addition, the method for introducing the metal when it is contained can be any of the methods of impregnation support, ion exchange, and physical mixing.
[0016] The metal-containing MFI zeolite of the present invention satisfies the above characteristics (i) to (vi), and the MFI zeolite refers to an aluminosilicate compound that belongs to the structure code MFI defined by the International Zeolite Association. The mesopores referred to in the present invention are mesopores defined by IUPAC and refer to pores with a pore diameter in the range of 2 to 50 nm. The mesopores can be measured by a general nitrogen adsorption method at liquid nitrogen temperature. The pore volume value of the mesopores can be obtained by analyzing the measurement results obtained by the nitrogen adsorption method. For example, the following method can be used for the analysis.
[0017] Specifically, the desorption process can be analyzed by the Barret-Joyner-Halenda method (Journal of the American Chemical Society, 1951, pp. 373-380). For example, by integrating the amount of nitrogen gas desorbed in the range corresponding to a pore diameter of 2 nm or more and 50 nm or less, the total pore volume of pores belonging to mesopores can be obtained.
[0018] In addition, first, a cumulative curve is obtained with the nitrogen desorption amount per unit mass V / m (mL / g) on the vertical axis and the mesopore diameter D (nm) on the horizontal axis, and then the vertical axis is changed to the differential value (d(V / m) / d(D)) of the nitrogen gas desorption amount from the mesopores with respect to the mesopore diameter value, whereby the peak of the increase in the nitrogen desorption amount per unit mass at the mesopore diameter can be obtained.
[0019] The metal-containing MFI zeolite of the present invention comprises an MFI zeolite having a group of mesopores with a nearly uniform pore diameter, and in the present invention, the group of mesopores with a nearly uniform pore diameter may be referred to as a uniform mesopore. Specifically, the uniform mesopore refers to a mesopore having a pore diameter within a range (μ±2σ) of twice the standard deviation (2σ) from the central value (μ) of the Gaussian function, which is obtained by approximating the maximum peak among the peaks related to mesopores in a pore distribution curve with a Gaussian function. The pore volume of the uniform mesopore can be calculated by integrating the amount of nitrogen gas desorbed within the range of μ±2σ.
[0020] The metal-containing MFI zeolite of the present invention includes, among MFI zeolites having a substantially uniform group of mesopores, (ii) an MFI zeolite having a more uniform group of mesopores, in which the mesopore distribution curve has a peak, the half width (hw) of the peak is hw≦20 nm, the center value (μ) of the peak is 10 nm≦μ≦20 nm, and the mesopore volume (pv) of the mesopores corresponding to the peak is pv≧0.05 ml / g.
[0021] The metal-containing MFI zeolite of the present invention has excellent reaction selectivity by containing an MFI zeolite having a peak in the pore distribution curve of the mesopores, the peak being an MFI zeolite having a group of almost uniform mesopores with small variation in the pore diameter size, that is, an MFI zeolite having hw≦20 nm or less, and the effect is more remarkable and preferable when hw≦15 nm, particularly hw≦10 nm. The lower limit of hw is not particularly set, but it is preferable that it is 1 nm or more because it will be more excellent in reaction selectivity. Note that if hw>20 nm, the reaction selectivity will be poor when used as a catalyst for producing hydrocarbon compounds. In addition, by containing an MFI zeolite having a center value (μ) of 10 nm≦μ≦20 nm when the peak is approximated by a Gaussian function, it becomes possible to selectively react even molecules of larger sizes, and it becomes an excellent catalyst for producing hydrocarbon compounds. Furthermore, by satisfying pv≧0.05 ml / g, the catalyst used will have a long life for producing hydrocarbon compounds, and 0.05 ml / g≦pv≦0.70 ml / g is preferable, 0.10 ml / g≦pv≦0.70 ml / g is particularly preferable, and 0.20 ml / g≦pv≦0.50 ml / g is even more preferable. Here, if pv<0.05 ml / g, the pores will be easily clogged due to the accumulation of coke and other by-products produced during the reaction, resulting in a poor catalyst life when used.
[0022] Furthermore, since the metal-containing MFI type zeolite of the present invention is particularly suitable as a catalyst for producing hydrocarbon compounds that enables selective reactions, it is preferable that the ratio (pvr) of pv shown in (ii) above to the total pore volume be 30%≦pvr≦100%, and it is more preferable that it be 40%≦pvr≦100%.
[0023] The metal-containing MFI zeolite of the present invention (iii) has no peak in the range of 0.1 to 3 degrees in powder X-ray diffraction measurement at a diffraction angle of 2θ. This indicates that there is no regularity in the arrangement of mesopores and no walls separating the mesopores, and when used as a catalyst, it facilitates material transfer between the mesopores, making it a catalyst for producing hydrocarbon compounds with excellent reaction efficiency.
[0024] The metal-containing MFI zeolite of the present invention is (vi) PD≦100 nm, and since it is particularly excellent in heat resistance, it is preferable that 3 nm≦PD, and more preferably 5 nm≦PD. Here, in the case of a zeolite with PD>100 nm, a group of substantially uniform mesopores is not formed, and the reaction selectivity is inferior when used as a catalyst for producing hydrocarbon compounds. As used herein, PD means Calculated from the external surface area using the following formula (1) do . PD=6 / S(1 / 2.29×10 6 +0.18×10 -6 ) (1) (Here, S is the external surface area (m 2 / g) In addition, the external surface area (S(m 2 / g) was calculated using a general nitrogen adsorption method at liquid nitrogen temperature and the t-plot method. demand. When t is the thickness of the adsorption amount, measurement points in the range of 0.6 to 1 nm for t are linearly approximated, and the external surface area is calculated from the slope of the obtained regression line.
[0025] As another method for measuring the particle diameter of the metal-containing MFI zeolite, for example, 10 or more particles are arbitrarily selected from a photograph taken with a scanning electron microscope (SEM) or a transmission electron microscope (TEM) and their surface area average diameter is calculated.
[0026] The metal-containing MFI type zeolite of the present invention is not limited in terms of its SiO2 / Al2O3 (molar ratio), and it is preferable that the SiO2 / Al2O3 (molar ratio) be 20 or more and 200 or less, since this will result in a catalyst for producing hydrocarbon compounds that is excellent in heat resistance, reaction selectivity, and productivity.
[0027] The metal-containing MFI type zeolite of the present invention is preferably one that does not contain a structure-directing agent such as tetrapropylammonium salt within the pores, since it serves as a catalyst for producing hydrocarbon compounds having excellent reaction selectivity and productivity.
[0028] As a method for producing MFI zeolite, which is a raw material that satisfies the above characteristics (ii) to (iv), the following method can be mentioned, for example.
[0029] Amorphous aluminosilicate gel is added to an aqueous solution of tetrapropylammonium (hereinafter sometimes referred to as "TPA") hydroxide and sodium hydroxide to form a suspension, and MFI type zeolite is added to the resulting suspension as seed crystals to form a raw material composition. The resulting raw material composition is crystallized and calcined to obtain MFI type zeolite.
[0030] The metal-containing zeolite of the present invention has (v) an outer surface acid amount of 0.0001 to 0.01 mmol / g. Here, the outer surface acid site of the zeolite, as the term implies, indicates an acid site present on the outer surface of the zeolite. Usually, a zeolite has acid sites on its outer surface and in (micro)pores, and the absence of acid sites on the outer surface means that the acid sites are present only in (micro)pores. In addition, it is preferable that the metal-containing zeolite has an unmodified surface that is not coated with silicate, dialkylamine reagent, etc., because it is the source of excellent heat resistance, hot water resistance, and durability. Here, when the outer surface acid amount is less than 0.0001 mmol / g, the catalyst performance of the catalyst in terms of production efficiency and selectivity when used as a catalyst for producing aromatic hydrocarbons is inferior. On the other hand, when it exceeds 0.01 mmol / g, the catalyst deterioration due to coking becomes significant when used as a catalyst.
[0031] The acid sites on the external surface of zeolites can be confirmed by any method that allows such confirmation. For example, they can be confirmed by adsorption of 2,4-dimethylquinoline, which has adsorptivity for acid sites (see Characterization of acid sites on the external surface of zeolites, Reaction Kinetics and Catalysis Letters, vol. 67, p. 281 (1999)).
[0032] The metal-containing zeolite of the present invention has an acid amount (vi) of 0.02 to 0.85 mmol / g, and preferably 0.02 to 0.55 mmol / g. The acid amount can be measured by a method generally known as a method for measuring acid amount, for example, a method based on the ammonia-TPD method (see Ammonia Temperature Programmed Desorption Method for Measurement of Solid Acidity, Catalysts, vol. 42, p. 218 (2000)). Here, if the acid amount is less than 0.02 mmol / g, the catalytic activity when used as a catalyst for producing aromatic hydrocarbons is poor. On the other hand, if it exceeds 0.85 mmol / g, the catalyst deterioration due to coking becomes significant when used as a catalyst.
[0033] As a method for producing such MFI zeolite satisfying (v) and (vi), for example, it is possible to produce it by dealuminating aluminum in the framework of MFI zeolite, which is a raw material satisfying the above characteristics (ii) to (vi), with steam or the like. The temperature of the steam treatment is, for example, preferably 400 to 900°C, particularly preferably 450 to 800°C, and more preferably 500 to 700°C. The partial pressure of the steam is preferably 0.001 to 5 MPa, particularly preferably 0.01 to 0.5 MPa, and more preferably 0.05 to 0.2 MPa. The concentration of the steam is preferably, for example, 0.01 to 100 vol% steam / dilution gas. The dilution gas may be an inert gas such as nitrogen, air, oxygen, carbon monoxide, carbon dioxide, or a mixture thereof. The steam treatment time can be selected arbitrarily.
[0034] The metal-containing MFI zeolite of the present invention can be produced by incorporating a metal into MFI zeolite by, for example, impregnation, ion exchange, physical mixing, or other methods.
[0035] The form in which the novel metal-containing MFI zeolite of the present invention is used as a catalyst for producing hydrocarbon compounds is not limited, and it is possible to use the metal-containing MFI zeolite powder as it is as a catalyst, to compress and mold it into a specific shape, or to mix it with a binder or the like and mold it into a specific shape, and so on.
[0036] By using the metal-containing MFI type zeolite of the present invention as a catalyst for producing hydrocarbon compounds, the catalyst becomes excellent in efficiency such as reaction selectivity and productivity, and by contacting it with, for example, an aliphatic hydrocarbon, particularly an aliphatic hydrocarbon having 10 or less carbon atoms, further an aliphatic hydrocarbon having 4 to 6 carbon atoms, it becomes possible to efficiently produce light hydrocarbon compounds and aromatic compounds simultaneously. In this case, the aliphatic hydrocarbons include, for example, paraffinic, olefinic, acetylene, and alicyclic hydrocarbons, and specific examples thereof include paraffinic, such as butane, isobutane, pentane, and hexane; olefinic, such as butene, isobutene, pentene, and hexene; alicyclic, such as cyclohexane, and mixtures thereof.
[0037] In the reaction according to the embodiment, the reaction temperature is not particularly limited as long as it is possible to produce aromatic compounds. In particular, the reaction temperature is preferably in the range of 400 to 800°C, since it suppresses the production of by-products such as paraffins, olefins, or alkanes and provides an efficient reaction between light hydrocarbon compounds and aromatic compounds without requiring an excessively high-temperature reaction apparatus. There is also no limitation on the reaction pressure, and operation is possible within a pressure range of, for example, about 0.05 MPa to 5 MPa. The supply of aliphatic hydrocarbons, which are the reaction raw materials, to the catalyst for simultaneous production of light hydrocarbon compounds and aromatic compounds is not particularly limited as the ratio of the volume of the raw material gas to the volume of the catalyst, and may be, for example, 1 h. -1 ~50000h -1 When the aliphatic hydrocarbon is supplied as the raw material gas, it may be used as a single gas, a mixed gas, or a gas diluted with a single or mixed gas selected from an inert gas such as nitrogen, hydrogen, carbon monoxide, and carbon dioxide.
[0038] The reaction type is not limited, and for example, not only fixed bed, transport bed, fluidized bed, moving bed, and multi-tubular reactor, but also continuous flow type, intermittent flow type, and swing type reactors can be used.
[0039] Examples of light hydrocarbon compounds produced include ethane, ethylene, propane, propylene, etc., with ethane and ethylene being particularly preferred. Examples of aromatic compounds are not particularly limited as long as they fall within the category of aromatic compounds, with benzene, toluene, xylene, trimethylbenzene, ethylbenzene, propylbenzene, butylbenzene, naphthalene, methylnaphthalene, etc. being particularly preferred. Effect of the Invention
[0040] The present invention relates to a specific MFI type zeolite containing a specific metal, which can be used as a catalyst for producing hydrocarbon compounds that can obtain a specifically long catalyst life, particularly when simultaneously producing light hydrocarbon compounds and aromatic compounds from aliphatic hydrocarbons, and is extremely useful industrially. EXAMPLES
[0041] The present invention will be specifically described below with reference to examples.
[0042] The performance of the MFI zeolite used in the examples as a catalyst for the simultaneous production of light hydrocarbon compounds and aromatic compounds was measured and defined by the following methods.
[0043] ~Measurement of pore distribution, pore diameter, and external surface area~ The pore distribution and pore diameter of the MFI zeolite were measured by nitrogen adsorption measurement.
[0044] The nitrogen adsorption was measured using a nitrogen adsorption apparatus (product name: OMNISORP360CX, manufactured by Beckman Coulter) at 30 torr / step for both adsorption and desorption. The external surface area was calculated by linear approximation in the range of the adsorption layer thickness (t=0.6-1.0 nm) using the t-plot method.
[0045] The desorption process of the nitrogen adsorption measurement was analyzed by the Barret-Joyner-Halenda method (Journal of the American Chemical Society, 1951, pp. 373-380), and a mesopore distribution curve was obtained in which the horizontal axis is the pore diameter constant and the vertical axis is the differential value of the desorption amount of nitrogen gas. The total pore volume of mesopores was calculated by integrating the amount of desorption of nitrogen gas in the range of 2 nm to 50 nm.
[0046] The maximum peak of the differential value (d(V / m) / d(D)) of the amount of nitrogen gas desorbed from the mesopores with respect to the mesopore diameter value was analyzed using the intensity approximation of a Gaussian function, and mesopores with diameters within a range of twice the standard deviation (2σ) (=μ±2σ) from the center value (μ) of the Gaussian function were defined as uniform mesopores. The pore volume of uniform mesopores was calculated by integrating the amount of nitrogen gas desorbed within a range of ±2σ based on the center value (μ).
[0047] ~Measurement of average particle size~ The average particle size was calculated from the external surface area using the above formula (1). In formula (1), S is the external surface area (m 2 / g), and PD is the average particle diameter (m). 2 / g) was calculated from the t-plot method using the nitrogen adsorption method at liquid nitrogen temperature.
[0048] ~Metal introduction amount measurement~ The amount of metal incorporated in the zeolite was determined by dissolving the MFI type zeolite in a mixed aqueous solution of hydrofluoric acid and nitric acid, and measuring the resultant solution by inductively coupled plasma atomic emission spectrometry (ICP-AES) using a general ICP apparatus (product name OPTIMA3300DV, manufactured by PerkinElmer).
[0049] ~Powder X-ray diffraction measurement~ An X-ray diffraction measurement device (Spectris, product name: X'pert PRO MPD) was used, and measurements were taken in air using CuKα1 at a tube voltage of 45 kV and a tube current of 40 mA. The range of 0.04 to 5 degrees was analyzed at 0.08 degrees / step and 200 seconds / step. In addition, the background corrected for the absorption rate of the direct beam was removed. The presence or absence of peaks was confirmed by visual inspection.
[0050] ~Measurement of the amount of outer surface acid~ The amount of external surface acid was measured by 2,4-dimethylquinoline adsorption infrared absorption spectroscopy. The measurement was performed by the transmission method using an FT-IR measurement device ((trade name) FT / IR-6700, manufactured by JASCO Corporation). The spectrum was obtained by 256 integration times using an MCT detector. The sample was molded into a disk with a diameter of 13 mm, and then placed in a disk holder in a quartz vacuum degassing cell, so that it was placed vertically on the infrared light path. As a pretreatment of the sample, the temperature was raised to 400°C at 10°C / min under vacuum evacuation and held for 2 hours. After cooling to 150°C, the infrared absorption spectrum before 2,4-dimethylquinoline adsorption was measured. 2,4-dimethylquinoline gas was introduced and adsorbed for 30 minutes, and after evacuation at 150°C for 1 hour, the infrared absorption spectrum after 2,4-dimethylquinoline adsorption was measured. The difference between the infrared absorption spectrum after 2,4-dimethylquinoline adsorption and the spectrum before adsorption was taken, and the change in infrared absorption due to adsorption was measured. In this difference spectrum, 3600 cm -1 The peak in this vicinity is the absorption spectrum peak of 2,4-dimethylquinoline adsorbed to the outer surface acid sites (Brønsted acid sites). After determining this integrated intensity, the amount of outer surface acid was calculated using the Lambert-Beerr law according to the following formula (2). Acid amount (μmol / mg)=A S / (W ε) Formula (2) (where A is the peak area intensity of the peak of interest (cm -1 ), S: sample cross-sectional area (cm 2 ), W is the sample weight (mg), ε is the integrated extinction coefficient, 3.7 cm μmol -1 , respectively.) ~Acidity measurement~ The amount of acid was measured by a method based on the ammonia-TPD method (see Measurement of solid acidity by ammonia temperature-programmed desorption method, Catalyst, vol. 42, p. 218 (2000)). The device used was a catalyst analyzer (trade name: BELCATII, manufactured by Microtrack Bell Co., Ltd.), and the sample was pretreated at 500°C for 1 hour under helium flow, and then ammonia was adsorbed at 100°C for 30 minutes. After that, the sample was treated at 125°C for 60 minutes under helium flow containing water vapor by passing through a bubbler, and the ammonia adsorbed at the weak acid site was removed. After that, the sample was purged at 100°C under helium flow, and the temperature was raised at 10°C / min under helium flow to measure the amount of thermal desorption. A quadrupole mass spectrometer (trade name: BELMASS, manufactured by Microtrack Bell Co., Ltd.) was used as the detector. The peak derived from the acid site near the desorption temperature of 370°C on the obtained temperature-programmed desorption curve was fitted with a Gaussian function, and the amount of ammonia desorbed was calculated from the area, thereby obtaining the amount of acid.
[0051] - Hydrocarbon compound manufacturing apparatus and manufacturing method thereof - The MFI type zeolite obtained in the examples and the catalyst for simultaneous production of light hydrocarbon compounds and aromatic compounds containing the same were used to produce light hydrocarbon products and aromatic compounds by the following methods, and the products were evaluated.
[0052] A fixed-bed gas-phase flow reactor using stainless steel reaction tubes (inner diameter 16 mm, length 900 mm) was used. The catalyst for simultaneous production was filled in the middle of each stainless steel reaction tube, and after performing a heating pretreatment under a dry air flow, the raw material gas was fed. The reactor equipment conditions and operating conditions are not limited to the conditions described in this example, and can be selected appropriately. A ceramic tubular furnace was used for heating, and the temperature of the catalyst layer was controlled. The reaction outlet gas and reaction liquid were collected, and the gas components and liquid components were analyzed individually using a gas chromatograph. The gas components were analyzed using a gas chromatograph (Shimadzu Corporation, (product name) GC-1700) equipped with a TCD detector. The packing material used was Waters' PorapakQ (product name) or GL Science's MS-5A (product name). The liquid components were analyzed using a gas chromatograph (Shimadzu Corporation, (product name) GC-2015) equipped with an FID detector. The separation column used was a capillary column (product name: TC-1, manufactured by GL Sciences).
[0053] The reaction conditions were set as follows:
[0054] (Conditions for producing hydrocarbon compounds) Catalyst temperature: 530℃. Gas flow: Mixture of 1-butene 125 ml / min, 2-butene 75 ml / min, isobutene 225 ml / min, normal butane 50 ml / min, and isobutane 25 ml / min. Catalyst weight: 70.0g. Reaction pressure: 0.1MPa.
[0055] Preparation Example 1 The MFI type zeolite was produced with reference to JP 2013-227203 A.
[0056] Amorphous aluminosilicate gel was added to an aqueous solution of tetrapropylammonium (hereinafter sometimes abbreviated as TPA) hydroxide and sodium hydroxide and suspended. MFI type zeolite was added to the resulting suspension as seed crystals to prepare a raw material composition. The amount of seed crystals added was 0.7% by weight relative to the weight of Al2O3 and SiO2 in the raw material composition. The by-product ethanol was removed by evaporation.
[0057] The composition of the raw material composition is as follows: SiO2 / Al2O3 molar ratio = 48, TPA / Si molar ratio = 0.05, Na / Si molar ratio = 0.18, OH / Si molar ratio = 0.20, H2O / Si molar ratio = 10 The obtained raw material composition was sealed in a stainless steel autoclave and crystallized for 4 days while stirring at 115°C to obtain a slurry mixture. After the crystallization, the slurry mixture was subjected to solid-liquid separation using a centrifugal settler, and the solid particles were washed with a sufficient amount of pure water and dried at 110°C to obtain a dry powder.
[0058] The obtained dry powder was dispersed in 1 mol / L hydrochloric acid at room temperature, filtered, the solid particles were washed with a sufficient amount of pure water, filtered again, and dried overnight at 100°C. It was calcined in air at 550°C for 1 hour, and then treated with 30% water vapor at 600°C for 2 hours. The obtained powder was dispersed in 1 mol / L hydrochloric acid at room temperature, filtered, the solid particles were washed with a sufficient amount of pure water, filtered again, and zeolite was obtained.
[0059] The obtained MFI type zeolite had an average particle size of 37 nm, an outer surface acid amount of 0.003 mmol / g, and an acid amount of 0.19 mmol / g.
[0060] Preparation Example 2 100 parts by weight of the MFI zeolite obtained in Preparation Example 1 were mixed with 43 parts by weight of silica (manufactured by Nissan Chemical Industries, (trade name) Snowtex N-30G), 4 parts by weight of cellulose, and 20 parts by weight of pure water. The mixture was then formed into a cylindrical shape with a diameter of 3.0 mm. This was dried overnight at 100°C, and then formed into a cylindrical molded body with a length of 4.5 to 8.5 mm (average length 6.6 mm). This was fired in air at 550°C for 1 hour. The obtained MFI zeolite had an average particle size of 34 nm, an outer surface acid amount of 0.003 mmol / g, and an acid amount of 0.14 mmol / g.
[0061] Example 1 100 g of the MFI zeolite molded body obtained in Preparation Example 2 was immersed in 264.3 g of 0.18 mol / L zinc nitrate aqueous solution for 30 minutes. After filtering the molded body, the temperature was raised to 110°C at a heating rate of 10°C / min and dried overnight, and then calcined at 550°C for 5 hours in an air stream to obtain a zinc-containing MFI zeolite. The zinc content of the obtained zinc-containing MFI zeolite was 0.5 wt%.
[0062] The obtained zinc-containing MFI type zeolite had a 10-membered ring framework structure, and the mesopore distribution curve in the pore distribution curve had a peak, and the half-width of the uniform mesopore peak was 9 nm, μ = 17 nm. The pore volume of the uniform mesopores was 0.34 ml / g, and the ratio of the pore volume of the uniform mesopores to the total pore volume of the mesopores was 80%. In the powder X-ray diffraction, there was no peak in the range of 0.1 to 3 degrees, the average particle size was 34 nm, the amount of outer surface acid was 0.003 mmol / g, and the amount of acid was 0.08 mmol / g.
[0063] The obtained zinc-containing zeolite was used as a catalyst for producing hydrocarbon compounds, and the reaction was carried out for 48 hours as described above. The average yield of each product during the reaction is shown in Table 1. The average yield of light hydrocarbon compounds (the total of ethane, ethylene, propane, and propylene) was 26.9% by weight, and the average yield of aromatic compounds (the total of benzene, toluene, and xylene) was 51.0% by weight. This product demonstrated an excellent balance as a catalyst for the simultaneous production of light hydrocarbon compounds and aromatic compounds.
[0064] Example 2 The same procedure as in Example 1 was carried out except that 75 g of the MFI zeolite molded body was immersed in 109.9 g of a 0.75 mol / L aqueous zinc acetate solution for 30 minutes, thereby obtaining a zinc-containing MFI zeolite.
[0065] The zinc content of the obtained zinc-containing MFI type zeolite was 2.6wt%, it had a 10-membered ring framework structure, the half-width of the uniform mesopore peak was 9nm, μ=17nm. The pore volume of the uniform mesopores was 0.34ml / g, and the ratio of the pore volume of the uniform mesopores to the total pore volume of the mesopores was 80%. In the powder X-ray diffraction, there was no peak in the range of 0.1 to 3 degrees, the average particle size was 34nm, the amount of outer surface acid was 0.003mmol / g, and the amount of acid was 0.08mmol / g.
[0066] The obtained zinc-containing zeolite was used as a catalyst for producing hydrocarbon compounds, and the reaction was carried out for 48 hours as described above. The average yields of each product during the reaction are shown in Table 1. The average yield of light hydrocarbon compounds (the total of ethane, ethylene, propane, and propylene) was 30.6% by weight, and the average yield of aromatic compounds (the total of benzene, toluene, and xylene) was 48.1% by weight. This product demonstrated an excellent balance as a catalyst for the simultaneous production of light hydrocarbon compounds and aromatic compounds.
[0067] Example 3 The same procedure as in Example 1 was carried out except that 75 g of the MFI zeolite molded body was immersed in 201.8 g of a 2.73 mol / L aqueous zinc nitrate solution for 30 minutes, thereby obtaining a zinc-containing MFI zeolite.
[0068] The zinc content of the obtained zinc-containing MFI type zeolite was 8.1wt%, it had a 10-membered ring framework structure, the half-width of the uniform mesopore peak was 9nm, μ=17nm. The pore volume of the uniform mesopores was 0.34ml / g, and the ratio of the pore volume of the uniform mesopores to the total pore volume of the mesopores was 80%. In the powder X-ray diffraction, there was no peak in the range of 0.1 to 3 degrees, the average particle size was 34nm, the amount of outer surface acid was 0.003mmol / g, and the amount of acid was 0.08mmol / g.
[0069] The obtained zinc-containing zeolite was used as a catalyst for producing hydrocarbon compounds, and the reaction was carried out for 48 hours as described above. The average yields of each product during the reaction are shown in Table 1. The average yield of light hydrocarbon compounds (the total of ethane, ethylene, propane, and propylene) was 30.0% by weight, and the average yield of aromatic compounds (the total of benzene, toluene, and xylene) was 45.7% by weight. This product demonstrated an excellent balance as a catalyst for the simultaneous production of light hydrocarbon compounds and aromatic compounds.
[0070] Comparative Example 1 The MFI zeolite obtained in Preparation Example 2 was used as a catalyst for aromatic production, and light hydrocarbon compounds and aromatic compounds were produced as described above. The results are shown in Table 1. The average yield of light hydrocarbon compounds (the total of ethane, ethylene, propane, and propylene) was 40.5% by weight, and the average yield of aromatic compounds (the total of benzene, toluene, and xylene) was 38.2% by weight. The yield of ethane in the light hydrocarbon compounds was low. In addition, the yield of aromatic compounds was low, and the balance of the yields of light hydrocarbon compounds was poor.
[0071] [Table 1] [Industrial Applicability]
[0072] The novel MFI zeolite of the present invention contains at least one metal selected from molybdenum, manganese, iron, cobalt, nickel, palladium, platinum, zinc, and gallium, and is characterized by having mesopores. This makes it possible to provide a stable production method with excellent productivity for each of the light hydrocarbon compounds and aromatic compounds, for example, when simultaneously producing them from aliphatic hydrocarbons, and is therefore extremely useful industrially as a catalyst for the simultaneous production of light hydrocarbon compounds and aromatic compounds.
Claims
1. A metal-containing MFI zeolite characterized by satisfying the following characteristics (i) to (vi): (i) The metal is zinc. (ii) The mesopore distribution curve has a peak, the half width (hw) of the peak is hw≦20 nm, the center value (μ) of the peak is 10 nm≦μ≦20 nm, and the mesopore volume (pv) of the mesopores corresponding to the peak is 0.05 ml / g≦pv. (iii) In powder X-ray diffraction measurement at a diffraction angle of 2θ, there is no peak in the range of 0.1 to 3 degrees. (iv) The average particle diameter (PD) is PD≦100 nm. (v) The amount of outer surface acid is 0.0001 to 0.01 mmol / g. (vi) the acid amount is 0.02 to 0.85 mmol / g.
2. 2. The metal-containing MFI zeolite according to claim 1, characterized in that the metal content is 0.05 to 15 wt %.
3. A catalyst for simultaneous production of light hydrocarbon compounds and aromatic compounds, comprising the metal-containing MFI zeolite according to claim 1 or 2.
4. A method for producing hydrocarbon compounds, comprising contacting an aliphatic hydrocarbon having 4 to 6 carbon atoms in the presence of the catalyst for simultaneously producing light hydrocarbon compounds and aromatic compounds according to claim 3 to produce C2 to C3 hydrocarbon compounds and aromatic compounds.
5. 5. The method for producing a hydrocarbon compound according to claim 4, wherein the C2 to C3 hydrocarbon compound is ethane, and the aromatic compound is one or more selected from the group consisting of benzene, toluene, and xylene.
Citation Information
Patent Citations
Pulse signal control circuit
JP1979047468A
Fish bait
JP1980064769A
Catalyst for producing aromatic hydrocarbon
JP1998033987A
Catalyst for aromatization reaction and method for producing aromatic hydrocarbon using the same
JP2006305408A
MFI type zeolite having uniform mesopore and method for producing the same
JP2013227203A